Heterologous phytase expression in the food filamentous fungus Aspergillus oryzae using the added rice husk cultivation model - Dung, Thai Hanh; Tuan, Tran Van (Academia Journal of Biology, 2020)
Aspergillus oryzae, a safe filamentous fungus, is widely used in food and enzyme production. In this study, we examined a cultivation model using rice husks as carrier to assess the capacity of recombinant protein production in A. oryzae. The model was first tested with the A. oryzae strain expressing the DsRed reporter gene. Expression of DsRed was easily detected by the pink color of the fungal mycelium on culture media and under a fluorescence microscope. The model was then evaluated with the phyA gene encoding a phytase from the fungus Aspergillus fumigatus. The phyA expression cassette regulated by the amyB promoter was permanently integrated into the genome of A. oryzae via Agrobacterium tumefaciens-mediated transformation with the pyrG nutritional marker. Results showed that A. oryzae transgenic strains carrying 2−3 copies of the phyA gene in their genomes exhibited a significant increase in phytase activity on agar medium supplemented with phytate. With rice husks added, these transgenic strains could secrete the recombinant phytase into the culture and phytase activity of the crude enzyme solution increased by 4.3 times compared to the unstransgenic A. oryzae. The established cultivation model and the transgenic approach in this study represent a potential for being used in production of secreted recombinant enzymes for animal feeds.